2014
DOI: 10.1155/2014/418690
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Polyphenol Components of Korean Prostrate Spurge (Euphorbia supina) by Using Liquid Chromatography—Tandem Mass Spectrometry: Overall Contribution to Antioxidant Activity

Abstract: The Korean prostrate spurge Euphorbia supina is a weed that has been used in folk medicine in Korea against a variety of diseases. Nine polyphenols were characterized for this plant by using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) and the results were compared with the literature data. The individual components were validated using the calibration curves of structurally related external standards and quantified for the first time by using the validated method. Correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
(37 reference statements)
2
23
0
Order By: Relevance
“…According to our results, 23 kinds of polyphenols were separated and identified, with quercetin and its glycosides being the principal component, having a relative percentage content of 25.93% in total. Our results were completely in accordance with some previous reports (Mario et al, ; Riffault et al, ; Song et al, ; Zhu et al, ). So, we used quercetin as the positive control in the following experiments of RAP activity determination.…”
Section: Discussionsupporting
confidence: 94%
“…According to our results, 23 kinds of polyphenols were separated and identified, with quercetin and its glycosides being the principal component, having a relative percentage content of 25.93% in total. Our results were completely in accordance with some previous reports (Mario et al, ; Riffault et al, ; Song et al, ; Zhu et al, ). So, we used quercetin as the positive control in the following experiments of RAP activity determination.…”
Section: Discussionsupporting
confidence: 94%
“…The thirty‐two polyphenols in the KAL were as follows: caffeic acid ( 1 ), syringic aldehyde ( 2 ), dicaffeoylquinic acid isomer ( 3 , 4 , 11 ), Quercetin 3‐O‐galactoside ( 5 ), dicaffeoylquinic acid isomer ( 6 ), mearnsetin 3‐O‐hexoside isomer ( 7 , 10 ), kaempferol 3‐O‐glucoside ( 8 ), quercetin 3‐O‐glucoside ( 9 ), ferulic acid ( 12 ), caffeoylferuloylquinic acid isomer ( 13 , 17–19 ), isorhamnetin 3‐O‐glucoside ( 14 ), diosmetin 7‐O‐glucoside ( 15 ), luteolin 7‐O‐glucoside ( 16 ), diferuloylquinic acid ( 21 ), quercetin ( 22 ), dicaffeoylferuloylquinic acid isomer ( 23 ), 3‐O‐methylquercetagetin ( 24 ), dicaffeoylferuloylquinic acid isomer ( 25 ), luteolin ( 26 ), 8‐methoxykaempferol ( 27 ), 3,5‐dimethoxyquercetagetin ( 28 ), caffeoyldiferuloyl quinic acid ( 29 ), kaempferol ( 30 ), 3,5‐dihydroxy‐6,7,4’‐trimethoxyflavone ( 31 ), and 3,5‐dihydroxy‐6,7,3’,4’‐tetramethoxyflavone ( 32 ). Quercetin and kaempferol derivatives formed 84.8% of the total polyphenols (Song et al, ). Twelve hydroxycinnamic acids ( 1 , 3 , 4 , 6 , 11 , 13 , 17–19 , 21 , 23 , and 25 ) and ten flavonoids ( 7 , 9 , 10 , 14 , 16 , 22 , 26 , and 30–32 ) were previously reported in Chinese, Brazilian, and Italian A. annua (Carbonara et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Polyphenols from E. supine (PES) were extracted and purified by Professor S.C. Shin as reported in Song et al (10). Briefly, the lyophilized E. supine tissue (10 g) was ground into powder and extracted in ethyl acetate (300 ml) at 80˚c for 20 h, and eluted using a mixture of methanol:dichloromethane (1:5, 25 ml).…”
Section: Preparation Of Polyphenol Mixtures Of Euphorbia Supine (E Smentioning
confidence: 99%
“…Epidemiological studies have shown that polyphenols reduce the risk of chronic diseases (7,8), and have anti-oxidant, anti-aging, and anti-microbial properties (9). According to Song et al (10), nine polyphenols have been isolated and identified from Korean E. supine, and quercetin and kaempferol derivatives account for 84.8% of the total polyphenols. Therefore, the inhibitory effects of E. supine on cancer growth and metastasis could be expected; however, few studies have been performed to demonstrate this effect.…”
Section: Introductionmentioning
confidence: 99%